Application of Cultured Epidermal Homograft (Kaloderm) for Wide Scar Treatment. Issue 6 (September 2019) - Lee, Joon Seok; Chu, Seung Gyun; Lee, Jeong Woo; Choi, Kang Young; Yang, Jung Dug; Cho, Byung Chae; Jeon, Saewha; Chung, Ho Yun
Abstract : Background: For the treatment of wide scars, laser resurfacing procedures are generally used. However, sometimes their results are not satisfactory. Many clinical studies have reported that cultured epidermal allogenic sheets promote rapid and good quality wound healing. Therefore, the authors applied a cultured epidermal homograft (CEH) for scar management and investigated its outcomes. Methods: Thirty-two patients who received a CEH (Kaloderm) after laser resurfacing (n = 14, under general anesthesia; n = 18, under local anesthesia) between February 2016 and June 2017 were enrolled. Patients treated with dermabrasion using laser resurfacing (n = 60) without CEH in the same period were used as controls. Clinical grading of the scars was performed using a Patient and Observer Scar Assessment Scale (POSAS) at postoperative 12 months. Results: The authors conducted a comparative analysis between the control and CEH groups. Evaluation based on Patient and Observer Scar Assessment Scale showed that the mean scores in control/CEH groups for the 7 observer components (vascularity, pigmentation, thickness, relief, pliability, surface area, and overall opinion) were 4.5/3.2, 3.3/2.8, 2.8/2.5, 3.6/3.5, 3.7/2.1, 2.3/1.9, and 3.2/2.7, respectively, with significant differences observed in vascularity, pliability, and surface area ( P values = 0.033, 0.021, and 0.048, respectively). Meanwhile, the mean scores in control/CEH groups for 7 patient components (pain, itching sense, color, stiffness, thickness, irregularity, and overall opinion) were 4.1/2.3, 3/3.1, 2.2/2.1, 2.2/1.7, 3.6/3.5, 1.8/1.5, and 2.2/1.9, respectively, with significant differences between groups observed in pain, stiffness, and overall opinion in the paired t test ( P values = 0.041, 0.020, and 0.048, respectively). Conclusion: Cultured epidermal homograft provided good quality wound healing and improved scar pliability. Cultured epidermal homograft left less scarring with no pain or other specific complications. Therefore, dermabrasion with CEH is useful for scar management. Abstract : Supplemental Digital Content is available in the text